IN TYPE 1 DIABETES MELLITUS, CAROTID INTIMA-MEDIA THICKNESS SHOWS DIFFERENCES BETWEEN GENDERS EARLY AFTER PUBERTY. (April 2021) - Bortolotti, Stefano; Tagetti, Angela; Giontella, Alice; Branz, Lorella; Marcon, Denise; Minuz, Pietro; Antoniazzi, Franco; Fava, Cristiano
Abstract : Objective: Type 1 diabetes mellitus (T1DM) is characterized by the early development of macrovascular damages in both genders but could manifest earlier in males. Traditional risk factors, along with T1DM per se, are associated with this process in T1DM. If specific differences in early vascular damage are viewable even during childhood in T1DM is unknown. Design and method: Arterial structural changes (carotid intima-media thickness [cIMT]) and vascular elasticity (carotid coefficient of distensibility [cDC] and Pulse Wave Velocity [PWV]) were measured in 180 children and adolescents with T1DM by carotid ultrasonography and the SphygmoCor XCel device. Hemodynamic and metabolic risk factors (peripheral and central systolic/diastolic blood pressure [pSBP/pDBP; cSBP], body mass index (BMI), glycated haemoglobin, triglycerides, total cholesterol, nonHDL/HDL-cholesterol ratio were also assessed. The sample was divided according to Tunner's stages (pre-pubertal-pubertal vs. post-pubertal) and gender: seventy-four subjects were classified as pre-pubertal-pubertal (44 male, mean age±SD 12 ± 2 years: 30 females, 12 ± 1.5 years) and 106 as post-pubertal (43 males, 16 ± 1 years; 63 females; age: 15.5 ± 1.5 years). Sex-specific linear regression models, adjusted for the pubertal state, BMI, duration of diabetes, glycated haemoglobin, nonHDL/HDL-cholesterol ratio, were constructed to assess the relation between risk factors and the markers of early vascular damage. Results: No differences in cIMT, cDC, PWV and the respective z-score were found between males and females in the pre-pubertal-prepubertal sub-group. In the post-pubertal group, males had higher cIMT (0.05 ± 0.01 mm; p-value: 0.001) and Z-score cIMT (0.62 ± 0.02; p-value: 0.04) but no differences in cDC and PWV were found. In linear regression models, the only risk factors independently associated with z-cIMT, were the nonHDL/HDL-cholesterol ratio (b ± SEM:0.267 ± 0.30; p-value:0.03) in males and z-cSBP in females (b ± SEM:0.286 ± 0.13; p-value:0.01). z-PWV and z-cDC showed associations with different types of BP values both in males and females. Conclusions: Gender-specific differences in cIMT are present early after puberty in adolescents with T1DM but seem associated with different risk factors in males and females. Different preventive strategies could be beneficial in males and females with T1DM, starting during adolescence.